The Beginning of Research On The Early Paleolithic Period - N. Abduvaliyeva (Genius Journals, 2024)
In the article, the study of the history of the Stone Age of Central Asia began in the years of the rule of the Russian Empire, the awakening of serious interest and attention to the remains of the Paleolithic culture, essentially, only coincided with the beginning of the 20th century. The history of the research of the lower layers of the Kolbuloq and Kyzylolma monuments in the Ohangaron river valley in the Tashkent region, the findings of Jarsoy, and the Bokantog monuments in the Kyzylkum region have been analyzed.
Keywords: Paleolithic; Neolithic; stone weapons